GAMBARAN PELAKSANAAN KONSELING KELOMPOK DENGAN TEKNIK REBT (RATIONAL EMOTIVE BEHAVIOUR THERAPY) DALAM UPAYA MENGATASI KECEMASAN MATEMATIKA SISWA SMP - Rahma Muti’ah (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: Mathematical learning anxiety (anxiety mathematic) has a very important role in mathematics learning activities. This is because the anxiety felt by students influences the students' concentration ability to take part in learning activities. Besides that mathematics anxiety also influences students' ability in understanding concepts and reasoning abilities which both of these aspects greatly influence the results of a student's mathematics learning. Mathematical anxiety can be derived from the irrational belief and emotional belief and students' mastery of the basic concepts of mathematics in calculating students. To overcome the above problems, the most appropriate solution to be used is the implementation of group counseling with the REBT technique, so that expectations with students' mathematical anxiety will be low so that student learning outcomes will increase.The method used in this study is descriptive qualitative. The population in this study were 115 students with high anxiety and low initial numeracy abilities. Consisting of 5 study groups, namely groups A, B, C, D and E, and the sample used was group A based on random results. Data collection tools used are observation and interviews, by testing the validity of the data using triangulation of sources (students, teachers and parents) and place.From the results of the implementation it was concluded that there was a decrease in mathematics anxiety of students after participating in group counseling activities with the REBT technique. The description of the implementation of group counseling with group REBT techniques consists of 5 stages of activity, namely 1) first meeting consisting of 4 steps, namely a) initial disputing, b) identification of self-condition, c) stop irrational belief and emotional belief, d) formulate thoughts and rational feeling about mathematics, 2) second meeting, namely a) persuasive stage, b) relaxation exercise, c) home work, 3) third meeting consists of 2 steps namely a) confrontation stage, and self talk writing, 4) fourth meeting namely a) working on the task and b) facing the real situation, 5) the fifth meeting namely a) homework discussion and b) conducting an evaluation. Keywords: REBT Counseling (Rational Emotive Behavior Theray), group, Mathematical Anxiety Abstrak Kecemasan belajar matematika (anxiety mathematic) memiliki peran yang sangat penting pada kegiatan pembelajaran matematika. Ini karena kecemasan yang dirasakan siswa mempengaruhi kemampuan konsentrasi siswa untuk mengikuti kegiatan pembelajaran. Selain itu kecemasan matematika juga mempengaruhi kemampuan siswa dalam pemahaman konsep dan kemampuan penalaran yang mana kedua aspek ini sangat mempengaruhi hasil belajar matematika seorang siswa. Kecemasan matematika bisa berasal dari irational belief dan emotional belief serta penguasaan siswa terhadap konsep-konsep dasar matematika siswa dalam berhitung. Untuk mengatasi permasalahan diatas maka solusi yang paling tepat digunakan adalah pelaksanaan konseling kelompok dengan teknik REBT, sehingga harapannya dengan kecemasan matematika siswa menjadi rendah maka hasil belajar siswa akan meningkat.Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Populasi dalam penelitian ini adalah 115 siswa dengan kecemasan tinggi dan kemampuan awal berhitung rendah. Terdiri dari 5 kelompok belajar yaitu kelompok A, B, C, D dan E, dan sampel yang digunakan adalah kelompok A berdasarkan hasil random. Alat pengumpul data yang digunakan adalah observasi dan wawancara, dengan pengujian keabsahan data dengan menggunakan triangulasi sumber (siswa, guru dan orangtua) dan tempat.Dari hasil pelaksanaan diperoleh kesimpulan terjadi penurunan kecemasan matematika siswa setelah mengikuti kegiatan konseling kelompok dengan teknik REBT. Adapun gambaran pelaksanaan konseling kelompok dengan teknik REBT kelompok terdiri dari 5 tahap kegiatan yaitu 1) pertemuan pertama yang terdiri dari 4 langkah yaitu a) disputing awal, b) identifikasi keadaan diri, c) menghentikan irrational belief dan emotional belief, d) merumuskan pemikiran dan perasaan yang rasional tentang matematika, 2) Pertemuan kedua, yaitu a) tahap persuasif, b) latihan relaksasi, c) home work, 3) pertemuan ketiga terdiri dari 2 langkah yaitu a) tahap konfrontasi, dan menulis self talk, 4) pertemuan keempat yaitu a) mengerjakan tugas dan b) menghadapi situasi nyata, 5) pertemuan kelima yaitu a) pembahasan homework dan b) melakukan evaluasi. Kata kunci: Konseling REBT (Rational Emotive Behaviour Theray), kelompok, Kecemasan Matematika